Biometric relation between body size and otolith size of Cyprinion kais and C. macrostomum collected from Tigris River, Şirnak Province, Türkiye - Dörtbudak Muhammed Yaşar; Jawad Laith A.; Yalçin Hamza; Park Joo Myun (Oceanological and Hydrobiological Studies)
One hundred and twenty asterisci were obtained from 30 specimens each of Cyprinion kais and Cyprinion macrostomum. Significant relationships between otolith mass and the three fish lengths (TL, SL, and FL) were attained for C. kais. Similar associations were obtained for OL and the three fish lengths of C. macrostomum. For C. kais, the highest in the relation between otolith mass, hereafter referred to as OM, and fish fork length, henceforth known as FL (0.5894). The lowest coefficient of determination was observed between otolith width, hereafter called OW, and standard fish length, hereafter referred to as SL (0.2861). For C. macrostomum, the highest coefficient of determination was attained for the relation between OL and FL (0.7280) and the lowest for the relationship between OM and TL (0.1717). The analysis shows that evaluations of the body size of the two fish species investigated through biometric studies of otoliths are trustworthy.